2008
DOI: 10.1100/tsw.2008.99
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Aspects of Mycolic Acids: An Important Target AgainstMycobacterium tuberculosis

Abstract: Mycolic acids are an important class of compounds, basically found in the cell walls of a group of bacteria known as mycolata taxon, exemplified by the most famous bacteria of this group, the Mycobacterium tuberculosis (M. tb.), the agent responsible for the disease known as tuberculosis (TB). Mycolic acids are important for the survival of M. tb. For example, they are able to help fight against hydrophobic drugs and dehydration, and also allow this bacterium to be more effective in the host's immune system by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Some antibiotics employed on tuberculosis treatment affect the metabolism of bacterial cell wall construction, which is a very important cellular component surrounding the cell membrane, providing additional support and protection (2). Basically, it is comprised of three covalently linked substructures: mycolic acids, peptidoglycan, and arabinogalactan, which represent over 60% of cell dry weight (3). The peptidoglycan is formed by extensive chains of polysaccharides and amino acid residues.…”
mentioning
confidence: 99%
“…Some antibiotics employed on tuberculosis treatment affect the metabolism of bacterial cell wall construction, which is a very important cellular component surrounding the cell membrane, providing additional support and protection (2). Basically, it is comprised of three covalently linked substructures: mycolic acids, peptidoglycan, and arabinogalactan, which represent over 60% of cell dry weight (3). The peptidoglycan is formed by extensive chains of polysaccharides and amino acid residues.…”
mentioning
confidence: 99%
“…This variety of lesions could be observed within a single individual patient simultaneously [39][40][41]. Due to their characteristic; these lesions will provide either false-positive or false-negative results on 99m Tc-ethambutol scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their characteristic; these lesions will provide either false-positive or false-negative results on 99m Tc-ethambutol scintigraphy. False-positive result could be caused by: (1) hypervascularization of non-specific infection or inflammation [30], (2) difficulties to get the adequate specimen [41], (3) and at least 10 4 number of acid-fast bacilli/mL of specimen culture are required to provide positive result [42,43]. In this study, we found 5 false-positive subjects: 3 subjects from the group of pulmonary TB and the other 2 subjects from the group of extra-pulmonary TB showed false-positive result.…”
Section: Discussionmentioning
confidence: 99%
“…The extremely hydrophobic envelope of mycolata is a permeable barrier which makes the bacteria highly resistant to the action of antibiotics and other chemotherapeutic agents ( 5 ). In the last decades several investigators have pointed out the existence of proteins playing a similar role to that of the porins of Gram-negative bacteria, facilitating the diffusion of hydrophilic solutes through the bacterial envelopes and the entry of antibiotics ( 6 , 7 ).…”
Section: Genome Announcementmentioning
confidence: 99%